PRARANCANGAN PABRIK AKRILONITRIL DARI ASAM SIANIDA DAN ASETILEN DENGAN KAPASITAS 50.000 TON/TAHUN - , ARIEF IMAM SANTOSO ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Preliminary design of acrylonitrile plant from cyanide acid and acetylene aims to examine the feasibility of the plant to be built. Acrylonitrile plant is designed with a capacity of 50,000 tonnes acrylonitrile/year starting in 2018 and operate continuously 330 days/year and 24 hours/day. To produce the required capacity, the raw materials needed are cyanide acid with quantity of 25.760,91 tonnes/year (99,5% (w/w)) and acetylene with quantity of 27.888,44 tonnes/year (99,5% (w/w)) respectively. Cuprous chloride dissolved in benzonitrile solvent is used as the catalyst for the reaction and the ratio of cuprous chloride to benzonitrile is maintained 35:65 (% weight). The reaction of acrylonitrile is conducted in a bubble column reactor equipped with stirrer. The operating conditions are pressure of 2 atm and temperature of 110 â°C. To obtain the products of acrylonitrile with purity of 99,6% (w/w), two distillation towers are used as the separation unit. The factory is planned to be built in Cilegon, Banten. The land area needed is 14.400 m2. The consumed energies are electricity of 34,44 million kWh/year, 3.159,82 m3/year of fuel oil, 17.194,53 kg/hour of make-up water, and 120 m3/hour of air instrument. The total employees needed including administrative and operating workers are 196 persons. Total capital invesment needed are fixed capital of $ 19,446,000 + Rp 12.715.349.000 and working capital of $ 11,347,000 + Rp 247.768.012.000. The acrylonitrile plant is classified as low risk chemical plant with ROI of 43,07 % (before taxes), 1,88 years of POT (before taxes), 45,88 % of BEP, 30,23 % of SDP, and 27,10 % of DCFRR. From the economical feasibility study, this factory is appealing for further studies.